Evaluation of MGA and Prostaglandin as an estrous synchronization procedure under field conditions - Houghton, P.L.; Corah, L.R.; Goehring, T.B. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
When fed MGA (0.5 mg.hd/day) for 14 days, followed by a prostaglandin injection 17 days later, a total of 736 out of 1112 heifers at 11 locations expressed signs of estrus within 5 days following the PG injection for a 66.2% response to synchronization. Response rates between locations ranged from 33 to 95% (P<.05). In a comparison of prostaglandin forms at 5 locations, using 789 heifers, response to synchronization was similar (P=.66) between Lutalyse® (62.7% response) and Bovilene® (59.6% response). First-service conception rate was compared in 411 heifers at two locations and was higher for Lutalyse (68.996) than Bovilene (59.996) (P<.08). First-service conception rate varied by technician (P<.05) and ranged from 48.7 to 83.6%.
Keywords: Beef; MGA; Prostaglandin; Estrous